Imaging in cellular and tissue engineering - Yu, Hanry; Abdul Rahim, Nur Aida. (Boca Raton : CRC Press, Taylor & Francis Group, 2013)
"This book covers the full range of available imaging modalities and optical methods used to help evaluate material and biological behavior. It also highlights a wide range of optical and biological applications. Each chapter in the text describes a specific application and discusses relevant instrumentation, governing physical principles, data processing procedures, as well as advantages and disadvantages of each modality. Following a broad introduction to key topics, the main chapters are divided between in vitro and in vivo applications. The final section focuses on methods for data processing and analysis"--Provided by publisher.
pt. 1. Overview -- pt. 2. In Vitro applications -- pt. 3. In Vivo applications -- pt. 4. Data analysis.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Microscopy; Tissue engineering; Medical technology; Electronic books